Subjective items to be considered in lipoabdominoplasty procedures under epidural anesthesia to increase their satisfaction - N. Mohammed, Haidar; A. Qaradaxi , Kurdo (Diyala Journal of Medicine, 2024)
Background: Patient satisfaction is increasingly recognized as a vital indicator of healthcare service quality. It aids in identifying healthcare system shortcomings and improving patient trust. Factors influencing patient satisfaction during anesthesia services have been studied globally, but there is a lack of research in the context of lipoabdominoplasty under combined lumbar spinal-epidural anesthesia (CLSEA). Objective: To evaluates patient satisfaction with lipoabdominoplasty under CLSEA, focusing on various intraoperative factors that may affect satisfaction. Patients and Methods: This prospective observational cross-sectional study included adult patients undergoing lipoabdominoplasty under CLSEA without complications. Patients completed a structured questionnaire assessing satisfaction with intraoperative care. The questionnaire addressed factors related to the information provided, decision-making involvement, physical comfort, emotional support, and respect for patient values. Results: The questionnaire encompassed three types of questions: anesthesia quality, factors causing intraoperative annoyance, and patient-team interaction. The majority of patients found epidural anesthesia favorable. Factors causing moderate annoyance included surgery duration, stress, fixed position, feeling cold, and shivering. Patients reported low annoyance with factors like team discussions, anxiety, surgical light, dizziness, thirst, itching, nausea, vomiting, noise, pain, and dyspnea. Patients generally had a high rate of good reactions toward the surgical team, but less than 50% requested more respect and thorough medication information. Conclusion: This study offers insights into patient satisfaction with lipoabdominoplasty under CLSEA, shedding light on factors affecting their experiences. The findings underline the importance of addressing patient concerns and expectations to enhance overall satisfaction and quality of care.